Association of temporal trends in neutrophil lymphocyte ratio on left ventricular assist device patient outcomes. Issue 7 (20th February 2021) - Solanki, Mitesh; Dobson, Lucas; Alwair, Hazaim; Ghafghazi, Shahab; Wysoczynski, Marcin; Slaughter, Mark S.; Trivedi, Jaimin R.
Abstract: Neutrophil to lymphocyte ratio (NLR) can predict mortality/complications in left ventricular assist device (LVAD) patients; however, the prognostic value of longitudinal NLR measurements has not been well studied. Here, we examine the mortality/complication incidence in patients with chronically increased NLR verses patients with acutely elevated NLR as a predictor of patient outcomes. This retrospective analysis included 102 patients who underwent LVAD implantation from 2016 to 2018 at a single center. The NLR was calculated at the time of surgery, and at 30 and 90 days after surgery. The NLR values were grouped into categorical data: low, normal (put in range), and high. Patients were classified in 2 groups based on change in their NLR values from surgery to 90 days; the H90 group had sustained increase of NLR over 90‐days and the N90 group had normalization of NLR at 90‐days. Actuarial survival the between study groups was measured using Kaplan–Meier curves. The N90 group had 50 patients (median age 58 (48–66) years, 21% female) at the time of LVAD placement. Group H90 had 52 patients (median age 64 (52–68) years, 16% female). Median age, body mass index (BMI), bilirubin, creatinine, and BNP at time of implant as well as type of device and implant strategy were comparable between the study groups. The post implant survival for N90 group was significantly better than the H90 group at 1 year (93% vs. 80%) and 2 years (90% vs. 67%) (log‐rank P  = .001). Early post LVAD survival in patients with elevated NLR over 90 days postoperatively was significantly worse compared to patients who normalized the NLR at 90 days.